(untitled) (Research, Society and Development, 2024)
Introduction: Non-Hodgkin’s lymphomas (NHL) are part of a heterogeneous group of malignant B and T cell tumors that arise in the lymph nodes (nodal) or in other locations, such as Peyer’s patches, spleen, tonsils, among others, where it is called extranodal. The objective of this article, therefore, is to spatially and quantitatively analyze cases of non-Hodgkin lymphoma in Brazil. Methodology: a descriptive cross-sectional epidemiological study was carried out based on the SUS health information department (DATA/SUS) using the variables: hospital admissions, mortality rate, deaths, age group, color/race, sex, type of care and health macro-region, average hospital stay. Results: 176,837 hospitalizations were obtained, with the Southeast region being most affected in relation to the number of hospitalizations, and the Central-West region being least affected. In line with the region with the most hospitalizations, the southeast region also presented the highest value of expenses and deaths. Furthermore, the most affected population were men, white and aged between 60 and 69 years. Conclusion: A scarce number of articles are seen on the epidemiology of NHL in Brazil. Therefore, greater investments in research related to this pathology and its ramifications are necessary.